Neglect and Detention of Messengers in Egypt during the Fourteenth and Thirteenth Centuries BCE - Abo-Eleaz, Mohy-Eldin E..
The present study explores and analyzes the relationships between countries of the ancient Near East by studying the complaints of neglect and detaining of foreign messengers and emissaries at the Egyptian royal court—and the courts of other the countries—during the fourteenth and thirteenth centuries BCE. This analysis also considers the traveling speeds of the messengers, the expected lengths of detention, and the credibility of the complaints of mistreatment and detention. The study reveals that the level of Egyptian maltreatment of the messengers of other countries reflected the significance and status of those countries at the Egyptian court. Moreover, messengers and envoys could be delayed or ill-treated for political and bureaucratic reasons, or issues related to crime and misconduct.